A Variant of the Larmor Frequency Calculation - Brtník, Bohumil; Matoušek, David (IEEE (Institute of Electrical and Electronics Engineers), 2024)
The Larmor frequency is a basic parameter in the design and calculation of elements, especially in microwave technology. Its value is usually derived using moments, but this calculation is both laborious and lengthy and does not lead to the correct result for ferrites. The article describes a more elementary procedure for finding the Larmor frequency based not on moments, but on the equality of force action. The latter is much shorter, clearer, and simpler, and it also gives a result that is in agreement with the experimentally verified quantum theory.
Varianta výpočtu Larmorovy frekvence
Keywords: Larmor frequency; gyromagnetic ratio; Larmorova frekvence; gyromagnetický poměr